A meta-analysis of factor effectiveness related to student's academic motivation - Pour, Marjan Karimi; Mohd Kosnin, Azlina; Mansor, Norwati (Serials Publication, 2017)
Motivation is recognized as a set of beliefs that drive and sustain behaviour and is an important precursor to learning and success in school (Kiefer, Alley, and Ellerbrock (2015). Motivation in learning has consistently been linked to reduced dropout and increased level of student success. The term motivation is often used to describe what gets people going, keeps them going, and helps them finish tasks (Pintrich, 2003b). This paper's principal statement refers to the factors that might influence student's academic motivation. Teachers play a vital role in supporting young adolescents' academic motivation. This paper provides an overview of factors that influence and effect student's academic motivation. The research methodology is based on a review of relevant literature search strategy through ERIC, online databases and journals such as Science Direct, Research in Middle Level Education Online, Springer Link, Taylor and Francis online, Indian journal of health and Journal of Psychology Education. The keywords used in the search included motivation, academic motivation, learning motivation, teacher support in motivation, motivational strategies, achievement motivation, motivation in primary school, motivation in secondary school and motivation in higher education, factors impact on motivation. The results of this meta-analysis show that a quantitative approach is largely the method used to analyse factor effectiveness for student's academic motivation. Findings from this review will lead teachers to investigate further on how to effectively implement improvements that influence motivation skills among students. © Serials Publications.